Endophthalmitis and COVID-19: A Narrative Literature Review - Gueorgui Markov; Rozalia Hristova; Nikolina Andonova; Yani Zdravkov; Alexander Oscar (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2022)
Endophthalmitis is a severe form of intraocular inflammation which is caused by bacteria or fungi. It is a medical emergency with an imminent threat to vision and permanent structural and functional complications. The condition affects the anterior and posterior segments of the eye. It may be either exogenous – following penetrating trauma or intraocular surgery, or endogenous, in which the pathogens enter the eye hematogenous. The diagnosis is based on the clinical picture and on specialized testing – aqueous and/or vitreous cultures, with or without additional PCR for panbacterial and panfungal primers. If endogenous endophthalmitis is suspected, blood and urine cultures may also be performed. The most common bacterial pathogens in acute postoperative endophthalmitis belong to the Staphylococcus and Streptococcus groups. Endogenous endophthalmitis is most frequently fungal and caused by Candida. The incidence of post-traumatic endophthalmitis ranges from 0.9 to 17% and of postoperative - from 0.016 to 5.7%, depending on the surgical procedure and the geographic location. Endogenous endophthalmitis has been observed in up to 8% of all cases. Therapy is urgent and may include intravitreal medications or pars plana vitrectomy (PPV), according to the Endophthalmitis Vitrectomy Study criteria. The combination of COVID-19-associated severe pneumonia, systemic corticosteroid therapy, and diabetes appear to be risk factors for endogenous endophthalmitis. The ethology has mostly been linked to fungal infections, especially Candida, as in the pre-COVID-19 era. There has been a tendency to perform PPV with intravitreal medications as the primary procedure, but the results have been mixed.